Singapore Clinical Practice Guidelines For Sarcopenia: Screening, Diagnosis, Management and Prevention - Lim, Wee Shiong; Cheong, C.Y; Lim, J.P; Tan, M.M.Y; Chia, J.Q; Malik, N.A; Tay, L (The Journal of Frailty & Aging, 2022)
AbstractObjectivesTo present the local evidence and final recommendations of the Clinical Practice Guidelines workgroup convened by the Chapter of Geriatricians and the Society for Geriatric Medicine Singapore. The aim is to develop contextualized evidence-based recommendations that facilitate adoption of the Asian Working Group for Sarcopenia (AWGS) 2019 consensus into current practice in Singapore. MethodsThe workgroup drew upon the AWGS'2019 consensus, updated literature review of Singapore studies till 31 Dec 2020, and evidence from recent systematic reviews. From 40 local studies included for data extraction, we constructed evidence tables organized as: definition and epidemiology; diagnosis and evaluation; and treatment and intervention. Twenty recommendations - case-finding, diagnosis, treatment, prevention, research - were developed, and graded for strength and quality using the GRADE approach. Consensus from an expert panel(N=23) was achieved after two rounds of the modified Delphi process. ResultsThe local prevalence of sarcopenia among community-dwelling older adults ranged from 13.6% to 25%. Most studies adopted the AWGS'2019 and AWGS'2014 criteria. Reported case finding tools include SARC-F, calf circumference (CC) and SARC-CalF. Gender-specific AWGS cut-offs for appendicular skeletal mass were used to define low muscle mass. Different protocols and dynamometers were used to assess handgrip strength, whilst gait speed and 5-times chair stand were commonly used to assess physical performance. RecommendationsWe conditionally recommend a case-finding approach in at-risk older adults using validated case-finding tools. Screen-positive individuals should be assessed for ‘possible sarcopenia' and underlying causes. For diagnosis, we conditionally recommend using the AWGS'2019 algorithm, and dual-energy X-ray absorptiometry when necessary to determine low lean mass for a confirmatory diagnosis of sarcopenia. For treatment, we strongly recommend resistance-based exercises and conditionally recommend a quality protein-rich diet/protein supplementation, with Vitamin D supplementation for insufficiency (<30 micrograms/L). For prevention, we recommend regular resistance-based physical activity and adequate protein intake (≥1.0g/kg bodyweight). We encourage more research to address local evidence gaps.